Virtual aspects of war strategy in the ХХІ century - Kirnitіkiy Oleg (Skhid, 2015)
The present paper examines the problem of modern world military thought. In the work the author focuses attention on the virtual component in the modern conflicts. Special attention author accentuates, for the mechanisms of formation the social foundations of a successful military action in the twenty-first century. The author pays special attention to the mechanism of formation of reality. Individually identifiable specific features relationship virtuality and war. The article shows the need for research on the theme of virtuality as a basis for social construction in the XXI century. The paper shows the philosophical foundation laid by under absolutely modern processes of virtualization. It is shown that the characteristics of virtual processes began to emerge in the late twentieth century. The author states that the processes of virtuality are key basics of any conflict of XXI century. Special relationship established between the concept of virtuality of the author and the concept of "hybrid warfare". The author gives all the logic deployment of process of virtuality to be able to show the features of the conflict in the Donbass. The author shows on the basis of virtual processes and predict the possibility of preventing similar conflicts in the future. Finally, the author indicates philosophical roots interrelation virtuality and modern war.